2022
DOI: 10.4274/tjo.galenos.2021.63255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Upper Eyelid Surgery on the Ocular Surface and Corneal Topography

Abstract: Objectives: To evaluate the effect of upper eyelid surgery on ocular surface and corneal topography. Materials and Methods: Patients who underwent upper eyelid blepharoplasty and/or blepharoptosis repair were evaluated prospectively. Tear film break-up time (TBUT), Schirmer tests, corneal staining pattern, Ocular Surface Disease Index questionnaire, corneal topography, and autorefractor parameters were measured preoperatively and at 1 day, 1 week, 1 month, 3 months, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Additionally, no significant differences were found in our study in pre-and post-operative keratometric values in patients who underwent ptosis and upper eyelid blepharoplasty procedures; likewise, no differences were detected in a study by Ceylan et al, who also reported significant changes in the K2 value in the first month in the Levator approach ptosis surgery group [17]. Considering that the patients were followed-up in the last 3 months in our study, it can be understood why no significant changes were detected in the keratometric values, given that the measurements yielded more accurate data over a longer period.…”
Section: Discussioncontrasting
confidence: 77%
“…Additionally, no significant differences were found in our study in pre-and post-operative keratometric values in patients who underwent ptosis and upper eyelid blepharoplasty procedures; likewise, no differences were detected in a study by Ceylan et al, who also reported significant changes in the K2 value in the first month in the Levator approach ptosis surgery group [17]. Considering that the patients were followed-up in the last 3 months in our study, it can be understood why no significant changes were detected in the keratometric values, given that the measurements yielded more accurate data over a longer period.…”
Section: Discussioncontrasting
confidence: 77%
“…Four previous reports have investigated anterior approach ptosis surgery and its effect on dry eye disease. 10,11,17,18 Watanabe et al, 11 evaluated tear meniscus radius and TBUT following levator aponeurosis advancement surgery using video meniscometry 1.5 months postoperatively. The authors concluded that there is a postoperative increase in tear film distribution and evaporation secondary to increased palpebral aperture.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of Eyelid Position: Dermatochalasis [5] and blepharoptosis [6] are upper eyelid disorders frequently encountered in ophthalmology. Treatment with upper eyelid blepharoplasty can lead to postoperative dry eye of varying severities.…”
Section: Preoperative Preventive Measures Postoperative Assessment An...mentioning
confidence: 99%
“…This may negatively affect tear production. Aksu Ceylan et al [6] found that upper eyelid blepharoplasty and levator advancement ptosis surgery led to a decrease in the Schirmer test results six months after the procedure. Studies have reported that dry eye and ocular irritation symptoms after upper eyelid blepharoplasty and blepharoptosis repair can regress within weeks after surgery [33,34].…”
Section: Preoperative Preventive Measures Postoperative Assessment An...mentioning
confidence: 99%
See 1 more Smart Citation